A review of the role of Malawi's law reform agency in criminalization and decriminalization of female same-sex sexual conduct. Issue 3 (3rd July 2019) - Kangaude, Godfrey Dalitso
Abstract: The Law Commission is an institution created by Malawi's 1995 Constitution with the mandate to review and recommend laws to be in conformity with the Constitution and international law. In 2000, the Commission recommended, for the first time in the history of Malawi, the criminalization of female same-sex sexual conduct. This was enacted into law in 2011. This article examines the role of the Commission in influencing the development of sex- and gender-related laws to address gender inequality and discrimination. It describes the historical context of legal developments since colonial times, leading to the adoption of a democratic constitution and commitment to incorporating human rights norms and standards in national laws. It argues that, in contradiction to its mandate, the Commission played an influential role in the development of a law that further marginalizes women and entrenches sex discrimination. It concludes that the Commission should therefore take responsibility for its actions and review the offending law sua sponte .